Integrasi Sistem Internasional Classification Primary Care Pada Rekam Medis Elektronik Berbasis Software As A Service Bagi Dokter Keluarga - Nuryati Nuryati; Dian Budi Santoso; Nur Rokhman (Politeknik Negeri Jember, 2023)
Referring to Law Number 29 of 2004 it is stated that every doctor or dentist in carrying out medical practice is obliged to make medical records. The results of the research on the readiness of ICPC implementation carried out in 2020 and the design of the interface for family doctor services equipped with the International Classification Primary Care (ICPC) carried out in 2021, the design was implemented and integrated in the Electronic Medical Record application with the concept of Software as a Services (SaaS) owned by the Department of Health Information and Services at the UGM Vocational School. This type of research is research and development by following the stages of developing an information system using the prototyping method. The steps taken in this research are conducting needs analysis through in-depth interviews with family doctors and medical record officers, in addition to conducting documentation studies and medical record observations conducted at family doctor clinics. The results of the analysis are ICPC codes in electronic medical records and interoperable with p-Care BPJS, so that family doctors only need to do data entry once, diagnosis code reports can be presented in the form of ICD-10 or ICPC code